Turkey between the Third World and the West: Consequences of Failing to Strike the Right Balance (1961–1965). Issue 3 (3rd July 2022) - Alim, Eray
Abstract: This article analyzes the reasons behind the Third World-averse and overtly pro-Western character of Turkish foreign policy by focusing on the period 1961–65. I argue that Turkey's lopsided foreign policy approach resulted from the failure to comprehend the advent of the Post-colonial phase of international relations and the leadership's dismissal of non-alignment as a policy strategy in world politics. These factors resulted in Turkey's overreliance on its alliance with the West through NATO. However, as the Cyprus Crisis of the early 1960s illustrates, the West was not always willing to support Turkey's position.